2011
DOI: 10.1002/adfm.201101963
|View full text |Cite
|
Sign up to set email alerts
|

Electroaddressing Functionalized Polysaccharides as Model Biofilms for Interrogating Cell Signaling

Abstract: Bacteria often reside at surfaces as complex biofilms in which an exopolysaccharide matrix entraps the population while allowing access to its chemical environment. There is a growing awareness that the biofilm structure and activity are integral to a wide array of properties important to health (the microbiome), disease (drug resistance) and technology (fouling). Despite the importance of bacterial biofilms, few experimental platforms and systems are available to assemble complex populations and monitor their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 42 publications
1
58
0
Order By: Relevance
“…We use chitosan primarily for the assembly of proteins to impart either selective binding properties [140] or enzymatic catalytic activities [141]. In contrast, when our goal is to assemble cells at electrode addresses, we generally favor alternative stimuli-responsive biopolymers such as alginate [78,[142][143][144][145][146], agarose [147] and gelatin [148]. Chitosan possesses several properties that facilitate protein assembly in/on an electrodeposited film through entrapment within the hydrogel network, covalent grafting to the polysaccharide backbone, or attachment through non-covalent associations.…”
Section: Biofunctionalizing Electrodeposited Chitosan Filmsmentioning
confidence: 97%
“…We use chitosan primarily for the assembly of proteins to impart either selective binding properties [140] or enzymatic catalytic activities [141]. In contrast, when our goal is to assemble cells at electrode addresses, we generally favor alternative stimuli-responsive biopolymers such as alginate [78,[142][143][144][145][146], agarose [147] and gelatin [148]. Chitosan possesses several properties that facilitate protein assembly in/on an electrodeposited film through entrapment within the hydrogel network, covalent grafting to the polysaccharide backbone, or attachment through non-covalent associations.…”
Section: Biofunctionalizing Electrodeposited Chitosan Filmsmentioning
confidence: 97%
“…"senders" and "receivers") at distinct addresses, and showed that they interacted across adjacent electrodes to deliver AI-2 and generate a fluorescence response. This concept has also been demonstrated by Cheng et al in a microfluidic chip 14 . We also mimicked the interaction, but instead used an enzyme to synthesize AI-2 for delivery.…”
Section: Discussionmentioning
confidence: 75%
“…First is the physical integration of these labile biological components into a functional system. Traditionally, integrated circuits are fabricated using thin film technologies and recent efforts are extending such technologies to the programmable assembly of biologically compatible hydrogels . Here, we electro‐assemble a dual hydrogel film system at an electrode surface.…”
Section: Methodsmentioning
confidence: 99%
“…After completing these electrofabrication steps, the dual film coating was stabilized by incubation in 1% CaCl 2 solution for 15 min (i.e., this step hardens the Ca 2+ ‐alginate hydrogel). Importantly, these electrofabrication steps are performed under sufficiently mild conditions to retain viability of the entrapped synbio components (e.g., E. coli cells) in the alginate hydrogel (see Figure S4, Supporting Information).…”
mentioning
confidence: 99%